Ilmu Hadist Dan Cabang-Cabangnya - Muhammad Ashar Malau (CV. SINAR HOWUHOWU, 2026)
Hadith science is an important branch of Islamic studies that focuses on the authenticity, transmission, and understanding of the hadiths of the Prophet Muhammad SAW. The purpose of this study is to identify the main branches of hadith science and explain their roles and contributions in preserving the purity of Islamic teachings. The method used is a literature study with a descriptive-qualitative approach, through analysis of relevant classical and modern literature. The results of the study show that hadith science has several main branches, including: Rijal al-Hadith (study of the biographies of narrators), Jarh wa Ta'dil (assessment of the credibility of narrators), Ilmu Takhrij (sanad tracing), Ilmu Mustalah al-Hadith (terminology and classification of hadith), and Ilmu 'Ilal al-Hadith (identification of hidden flaws in hadith). Each branch has a specific role in evaluating the authenticity and quality of hadith, and they complement each other in the verification process.